Upcoming Drifts in Bio-similars - Aggarwal, Geeta; Nagpal, Manju; Sharma, Ameya; Puri, Vivek; Dhingra, Gitika A. (Current Reviews in Clinical and Experimental Pharmacology, 2021)
Background: Biopharmaceuticals such as biological, medicinal products have been in clinical use over the past three decades and have benefited the therapy of degenerative and critical metabolic diseases. It is forecasted that the market of biologics will be going to increase at a rate of > 20% per year, and by 2025, more than 50% of new drug approvals might be biological products. The increasing utilization of the biologics necessitates cost control, especially for innovator products that have a lengthy period of exclusive usage. As the first wave of biopharmaceuticals is expired or set to expire, it has led to various opportunities for the expansion of bio-similars i.e. copied versions of original biologics with same the biological activity. Development of biosimilars is expected to promote market competition, meet worldwide demand, sustain the healthcare systems and maintain the incentives for innovation. Methods: Appraisal of published articles from peer-reviewed journals, PubMed literature, latest news and guidelines from European Medicine Agency, US Food Drug Administration (FDA) and India were used to identify data for review. Results: Main insights into the quality requirements concerning biologics, the current status of regulation of bio-similars and upcoming challenges lying for the upgrading of the marketing authorization of biosimilars have been incorporated. Compiled literature on the therapeutic status, regulatory guidelines and the emerging trends and opportunities of biosimilars has been thoroughly stated. Conclusion: Updates on biosimilars will support to investigate the possible impact of bio-similars on the healthcare market.
Keywords: Biologics